Combined therapy with ivermectin and doxycycline can effectively alleviate the cytokine storm of COVID-19 infection amid vaccination drive: A narrative review. Issue 5 (May 2022) - Sharma, Satish Kumar; Bhatt, Pankaj; Asdaq, Syed Mohammed Basheeruddin; Alshammari, Mohammed Kanan; Alanazi, Abeer; Alrasheedi, Naif Saleh; Alrashdi, Bader Abdullah; Alyami, Saad Saleh; Alhazmi, Bshayer Hamdan; Alam, Perwaiz; Sharma, Prerna; Tomar, Ritu; et al.
Abstract: An unprecedented global health crisis has developed due to the emergence of the mysterious coronavirus-2 of the severe acute respiratory syndrome, which has resulted in millions of deaths around the globe, as no therapy could control the 'cytokine storm'. Consequently, many vaccines have been developed and several others are being developed for this infection. Although most of the approved vaccines have been highly effective, many developing, and economically poor countries are still deprived of vaccination against SARS-CoV-2 due to the unequal distribution of vaccines worldwide. Furthermore, the uncertainty about the effectiveness of the available vaccines against the emerging mutants and variants also remains a matter of concern. Due to the multistep pathogenesis and unique features, combination therapy using safe immunomodulatory and antiviral drugs should be considered as the most effective and acceptable therapeutic regimen for this infection. Based on a thorough assessment of the literature, it was determined that it would be interesting to study the therapeutic potential of ivermectin and doxycycline, given their roles in several biological pathways involved in SARS CoV-2 pathogenesis. Following that, a comprehensive literature search was undertaken using Scopus, Web of Science, and Pubmed, depending on the inclusion and exclusion criteria. The present study provides a mechanism and comprehensive report, highlighting the role of combined therapy with ivermectin and doxycycline in alleviating the 'cytokine storm' of COVID-19 infection.